Leopoldo María Panero, Mallorca, 1977: the glimpsed death. An unpublished text of the narration of the episode (and two more) - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This paper presents a group of unpublished texts by Leopoldo María Panero in which the poet gives an account of the “persecutions” to which he was subjected throughout his life, and which are symptoms of a more than evident paranoia. However, Panero made this paranoia a conscious element of his poetics, marking it rhetorically as a hyperbolic overinterpretation of reality.
Keywords: Leopoldo María Panero; psychology; paranoia